Investigation of higher education students' learning styles and attitudes towards mobile learning according to various variables - Tuncer, Murat; Dikmen, Melih; Akmençe, Ahmet Egemen (My University, 2018)
The purpose of this study is to examine students' learning styles and their attitudes towards mobile learning. In this study, a screening model was used to describe the existing situation. In this context, research was conducted on 209 undergraduate students at Fırat University. To collect data, Kolb Learning Styles Inventory developed by Kolb and adapted to Turkish by Evin Gencel was used. The Mobile Learning Attitude scale developed by Demir and Akpınar was used to examine students' attitudes toward mobile learning. When the findings were examined, it was determined that 46.4% of the students had Assimilator, 25.8% of them Divergers, 14.8% of them Convergers and 12.9% of them had Accommodator learning style. The students with the highest attitude towards mobile learning were found to have a Converger learning style. It was determined that the students with the lowest attitudes towards mobile learning had a Diverger learning style. Among the important characteristics of the individuals with a Converger learning style are shown to prefer to work individually in learning activities. It can be said that individuals who have a Converger learning style are positively influenced by their attitudes toward mobile learning, because many applications on mobile learning platforms allow individual learning.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Mobile learning attitude; Learning styles; Higher education students; Kolb learning style